Capitalism and its critics - Delanty, Gerard, author.
1 online resource
Keywords: "Capitalism and its Critics offers an accessible account of major theories of capitalism from the industrial revolution to the present day. The book provides a comprehensive account of the economic and social thought of key theorists from Adam Smith and Karl Marx to David Harvey and Thomas Piketty. Capitalism has long been the subject of passionate debate, and today such contestations are perhaps more timely than ever. For its advocates, capitalism brings democracy and freedom and is the cornerstone of modernity and of progress. For its critics, capitalism is based on the exploitation of labour and is responsible for the destruction of the environment as well as colonialism. Whether capitalism survives the century, or whether an alternative social system emerges, may very well determine the fate of humanity. Capitalism and its Critics gives a comprehensive critical analysis of the most important theorists of capitalism, including Adam Smith, Karl Marx, Max Weber, Joseph Schumpeter, Karl Polanyi, F.A. Hayek, J.M. Keynes, David Harvey, and Thomas Piketty. The book discusses some of the main debates about capitalism and considers alternatives in the twenty-first century. The twelve chapters are loosely chronologically organised around the main approaches and historical phases in the history of capitalism. Central themes of the book are the ideas of capitalist crisis and of tensions between democracy and capitalism in the making of modernity. A highly readable, informative and engaging text, Capitalism and its Critics is essential reading for anyone interested in understanding capitalism and its alternatives"--